Conceptual Framework of an Effective Decision Support System in Forest Fire Management - Kadir Alperen Coşkuner; Ertuğrul Bilgili (Doğal Afetler ve Çevre Dergisi)
Forest fire management organizations require accurate, timely and readily available information to be successful in forest fire suppression. A sound decision support system is necessary to acquire and make this information available to fire management organization. In this study, the framework, structure and hierarchy of a Decision Support System (DSS) was designed in forest fire management organization and planning in Turkey. DSS consists of four subsystems which can operate individually or collectively. These subsystems are; i) Fire Information System; a smart database for fire managers to input, store, update and manage data easily, ii) Fire Occurrence Prediction System; forest fire risk and danger determiner using constant environmental variables iii) Fire Weather Index System; fire weather index calculator for the ignition potential of fuels, potential rate of spread and fire intensity, iv) Fire Behavior Prediction System; fire propagation simulator for predicting fire behavior under varying weather, fuel and topographic conditions. When readily available for operational use, the DSS will have the potential to provide fire managers with tools and support necessary for successful fire prevention/presuppression, suppression and post fire management planning.